The Influence of Deposit Fee And Late Fine On Customer Satisfaction of Bsi Gunung Tua Gold Pawn - Bana Darwisah Pohan; Tuti Anggraini (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2023)
This study aims to understand the effect of safekeeping fees (ujrah) and fines for late payment of gold pawn products on customer satisfaction at Bank Syariah Indonesia (BSI) KCP Gunung Tua. This type of research is quantitative research with the sample is 95 respondents. Using data collection techniques in the form of a questionnaire. Data analysis is using, namely the Validity test, reliability test, normality test, classic assumption test, multiple linear regression analysis, partial test (t test), simultaneous test (F test), and test the coefficient of determination (R2). From the results of the study it was concluded that together with the cost of safekeeping (ujrah) and late payment fines for gold pawn products, they have an effect and are partial to gold pawn customer satisfaction. Simultaneously, the value of Sig. namely 0.000 <0.05 and fcount 42.020 > ftable 3.10. Partially, the value of Sig. X1 = 0.000 and X2 = 0.000, then the value of both <0.05 and with tcount X1 = 3.156 and X2 = 4.187 > ttable 2.604.